2018
DOI: 10.7754/clin.lab.2017.170731
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs as Potential Biomarkers in Gastrointestinal Tract Tumors: Opportunities and Challenges

Abstract: Most digestive system tumors have poor prognoses due to the lack of specific biomarkers. Circular RNAs (circRNAs) regulate the expression of genes and play essential roles in digestive system tumorigenesis. Here we review circRNA functions in gastrointestinal tract tumors. CircRNAs are promising biomarkers for clinical applications for gastrointestinal tract tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…72 fIGURE 1. miRNA expression in the most common cardiovascular diseases (CVDs). 56,[58][59][60][61][62][63][64][65][66] Moreover, numerous studies demonstrated that the activity of NF-κB has important implications on the he- in CVDs. From a molecular point of view, in the activation of TLR4 intervenes the myeloid differentiation factor 81 (MyD88), which is responsible of the connection between Toll/Interleukin-1 (Toll/IL-1) receptor (TIR) and TLR4.…”
Section: Mirnas and Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 fIGURE 1. miRNA expression in the most common cardiovascular diseases (CVDs). 56,[58][59][60][61][62][63][64][65][66] Moreover, numerous studies demonstrated that the activity of NF-κB has important implications on the he- in CVDs. From a molecular point of view, in the activation of TLR4 intervenes the myeloid differentiation factor 81 (MyD88), which is responsible of the connection between Toll/Interleukin-1 (Toll/IL-1) receptor (TIR) and TLR4.…”
Section: Mirnas and Acute Myocardial Infarctionmentioning
confidence: 99%
“…shows the most important changes in miRNA expression in the most common cardiovascular diseases 56,[58][59][60][61][62][63][64][65][66]. Nf-κB, INfLAmmATION, AND ATHEROSCLEROSISAnother important factor involved in the molecular mechanisms that lay at the basis of cardiovascular dis-eases is represented by nuclear factor kappa B (NF-κB) 15.…”
mentioning
confidence: 99%
“…It has been demonstrated that circRNAs have regulatory roles in the expression of genes by binding to miRNAs, suggesting the important role of circRNA-miRNA-mRNA interaction networks in the occurrence and development of human digestive system tumors, thus highlighting their potentials as diagnostic biomarkers (25). For instance, hsa_circRNA_103809 participates in the modulation of biological functions through the miR-532-3p/FoxO4 axis in colorectal cancer (5).…”
Section: Discussionmentioning
confidence: 99%